2017
DOI: 10.1177/1010428317698377
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA urothelial carcinoma-associated 1 overexpression as a poor prognostic biomarker in clear cell renal cell carcinoma

Abstract: Long noncoding RNA urothelial carcinoma-associated 1 has previously played important roles in cancer. However, its role is still unknown in clear cell renal cell carcinoma. We utilized the most recent molecular and clinical data of clear cell renal cell carcinoma from The Cancer Genome Atlas project, and the relationship between urothelial carcinoma-associated 1 expression and the clinicopathological features was analyzed. Our results indicated that urothelial carcinoma-associated 1 overexpression was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…As an example, in metastatic ccRCC tissues, lncRNA termed metastatic renal cell carcinoma-associated transcript 1 (MRCCAT1) is ectopic upregulated, which might cause the metastatic capacity of ccRCC via mediating associated signalling transduction systems [18]. Besides, lncRNA UCA1 is overexpressed in ccRCC and the overexpression of UCA1 has been regarded as a poor prognostic biomarker in ccRCC diagnosis [19]. In our present study, we found LINC01939 was obviously downregulated in RCC tissues.…”
Section: Discussionmentioning
confidence: 49%
“…As an example, in metastatic ccRCC tissues, lncRNA termed metastatic renal cell carcinoma-associated transcript 1 (MRCCAT1) is ectopic upregulated, which might cause the metastatic capacity of ccRCC via mediating associated signalling transduction systems [18]. Besides, lncRNA UCA1 is overexpressed in ccRCC and the overexpression of UCA1 has been regarded as a poor prognostic biomarker in ccRCC diagnosis [19]. In our present study, we found LINC01939 was obviously downregulated in RCC tissues.…”
Section: Discussionmentioning
confidence: 49%
“…RCC is one of the most common malignancies, and ccRCC represents the majority of RCC. ccRCC patients can show different clinical manifestation and treatment response because of the tumor heterogeneity in histology, oncogenicity and molecular alterations in tumor suppressor genes [ 24 ]. Furthermore, previous reports have shown that the mutations on Von Hippel-Lindau ( VHL ), Polybromo-1 ( PBRM1 ) and BRCA1 associated protein-1 ( BAP1 ) are the most common somatic mutations in ccRCC which induces the occurrence and development of ccRCC [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of lncRNA biology, a growing number of functional lncRNAs in RCC progression have been identified. In patients with RCC, the dysregulation of lncRNAs can promote the progression of RCC, resulting in poor prognosis (31)(32)(33). RCC tumorigenesis is a complex biological process that involves not only mutations in genetic networks but also epigenomic alterations that can trigger imbalances in cellular homeostasis and ultimately lead to abnormal cell growth.…”
Section: Introductionmentioning
confidence: 99%